The Effect of Celebrity Endorsement, Credibility, Attractiveness, and Trustworthiness on Product Purchase Intention with Mediation Perceived Quality - Selvi, Selvi; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2026)
This study aims to analyze the influence of celebrity endorsement, celebrity credibility, attractiveness, and trustworthiness on the purchase intention of Indonesian cosmetic products, with perceived quality as the mediating factor. The method used was a quantitative survey, collecting data through an online questionnaire from 150 respondents who use local cosmetic products residing in Jakarta Indonesia. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results showed that attractiveness, celebrity endorsement, celebrity credibility, attractiveness, and trustworthiness had a positive and significant effect on purchase intention. Furthermore, perceived quality mediated the influence of all four independent variables on purchase intention. These findings indicate that perceived quality plays a significant role in bridging the influence of endorser characteristics on consumer purchase intention. This study is expected to provide theoretical contributions to the development of marketing literature, particularly regarding celebrity endorsements, and provide practical implications, for local cosmetic companies in designing effective promotional strategies to increase consumer purchase intention, with the market in Indonesia.